Circ-CSNK1G1 promotes cell proliferation, migration, invasion and glycolysis metabolism during triple-negative breast cancer progression by modulating the miR-28-5p/LDHA pathway - Xiaochen Zan; Wenfang Li; Geng Wang; Jie Yuan; Yongbiao Ai; Jun Huang; Zhi Li (BMC, 2022)
Highlights 1. Circ-CSNK1G1 is upregulated in TNBC. 2. Circ-CSNK1G1 knockdown inhibits the proliferation, migration, invasion and glycolysis energy metabolism of TNBC cells. 3. Circ-CSNK1G1 knockdown inhibits tumor formation in vivo. 4. Circ-CSNK1G1 promotes TNBC development by regulating the miR-28-5p/LDHA pathway.